Middle Armenian Word Formation Patterns with Bases Borrowed from Georgean - GRIGORYAN, SUSANNA (Bulletin of Yerevan University B: Philology, 2021)
There are loan words borrowed from Georgian in the vocabulary of Middle Armenian, which entered the language in both written and oral ways. The loan words are taken from the foreign language with their own meaning and phonetic peculiarities, but can later undergo affixation or compounding in the borrower language. This kind of compound and derivative words are considered to be hybrid formations in the language. The separation of loan words from Georgian within word compositions is very important because it decides the frequency and usage of the given loan word which is essential for the estimation of the value of borrowings in general.